Enhancing Students’ Motivation in Islamic Religious Education Through Teacher Parent Collaboration: Evidence from an Indonesian Elementary School - Harni Kadang; Andi Abd Muis; Suredah Hamid; St. Warda Hanafie Das; Muhammad Naim (CV. Gerasi Insan Nusantara, 2026)
This study examines students’ learning motivation in Islamic Religious Education (IRE), the implementation of a collaborative learning model between teachers and parents, and the role of such collaboration in enhancing students’ motivation at UPTD SDN 18 Kalosi Enrekang. The study aimed to describe students’ learning motivation in IRE, analyze the implementation of teacher–parent collaborative learning, and explain its contribution to improving students’ motivation. This research employed a qualitative approach with pedagogical, psychological, and theological perspectives. The study was conducted over three months at UPTD SDN 18 Kalosi Enrekang. Primary data were obtained from the principal, teachers, parents, and students, while secondary data were collected from school documents and relevant literature. Data were gathered through observation, interviews, and documentation and analyzed using data reduction, data display, and conclusion drawing. Data validity was ensured through triangulation, member checking, prolonged observation, and persistent observation. The findings indicate that students’ learning motivation in IRE is generally good, particularly in practical topics such as prayer, worship practices, and moral values. However, motivation tends to decrease when students encounter more theoretical subjects, including tafsir and fiqh. The study also found that collaboration between teachers and parents positively affects students’ learning motivation. Active parental involvement in supervising learning at home and maintaining regular communication with teachers strengthens students’ enthusiasm, discipline, and engagement in learning. This study contributes to the growing literature on school–family partnerships by demonstrating how teacher–parent collaboration strengthens learning motivation within the context of Islamic Religious Education in elementary schools.